ON THE ROLE OF PARLIAMENT IN IMPROVING PUBLIC GOVERNANCE - Sufiyeva Dilafruz Ulugbekovna (Modern American Journals, 2025)
The article examines the role of parliament in implementing administrative reforms. The article emphasizes the need for active participation of the chambers of parliament in implementing administrative reforms. At the same time, the article notes the advisability of regulating issues related to public administration at the legislative level. The article also notes the role of parliament in promoting good public administration requires a correct understanding of the concept of effective public administration.
Keywords: Public administration, parliament, separation of powers, principle of checks and balances between branches of government, legislative power, executive power, administrative reform, optimization of executive bodies, parliamentary control, concept of effective public administration.